Inherited prion disease (PrP lysine 200) in Britain: two case reports. Issue 6873 (30th January 1993) - Collinge, J; Palmer, M S; Campbell, T; Sidle, K C; Carroll, D; Harding, A
Abstract : OBJECTIVE--To identify cases of inherited prion diseases in Britain and to assess their phenotypic features. DESIGN--Screening study of patients suspected clinically to have Creutzfeldt-Jakob disease and other neurodegenerative diseases by prion protein gene analysis. SETTING--Biochemical research department. SUBJECTS--Patients suspected to have Creutzfeldt-Jakob disease and other neurodegenerative diseases. RESULTS--Two patients with symptoms characteristic of sporadic Creutzfeldt-Jakob disease were found to have inherited prion protein disease (PrP lysine 200), with a mutation at codon 200 of the prion protein gene. Both were homozygous at codon 129 of the gene. One patient was a man aged 58 of British descent while the other was of Libyan Jewish origin. CONCLUSION--Two foci of inherited prion disease are known, among Libyan Jews and in Slovakia. A separate British focus of the disease may also exist. Heterozygosity at codon 129 may lead to reduced penetrance of the mutation.